Design Educational Bag in Basics of Image Processing - Ghada Tahir Qasim (Al-Rafidain Journal of Computer Sciences and Mathematics)
The didactic bags which are programs designed to replace the teacher in a certain scientific field, are the modernist didactic means which proved great activity in the didactic process and due to the importance of the images processing field of computers, so It has been constructed in this paper on designing of didactic bag in the bases of the images processing field which is considered as one of the classification of computer imaging. The research deals with the images processing in that the idioms. It deals the most famous idioms of images processing. It also treats of some of the images folders shapes. It deals with parts of images processing in detail as well as giving instance to illustrate each of these parts. It deals with the associating process with the parts of the images processing in that digital filtration and mathematical rolling, besides it deals with the special commands in the images processing in some programming languages as Matlab language, c++ language and visual basic language with giving some instances. The paper also contains a show for some internet sites in order to give the opportunity to the user to increase his knowledge and expertise if he wishes to sight the internet sites.